To the end of June : the intimate life of American foster care - Beam, Cris (Mariner Books : Houghton Mifflin Harcourt, 2014)
Who are the children of foster care? What, as a country, do we owe them? The author, a foster mother herself, spent five years immersed in the world of foster care, looking into these questions and tracing firsthand stories. The result is this work, an unforgettable portrait that takes us deep inside the lives of foster children at the critical points in their search for a stable, loving family. The book mirrors the life cycle of a foster child and so begins with the removal of babies and kids from birth families. There's a teenage birth mother in Texas who signs away her parental rights on a napkin only to later reconsider, crushing the hopes of her baby's adoptive parents. She then paints an unprecedented portrait of the intricacies of growing up in the system, the back-and-forth with agencies, the shuffling between pre-adoptive homes and group homes, the emotionally charged tug of prospective adoptive parents and the fundamental pull of birth parents. And then what happens as these system-reared kids become adults? The author closely follows a group of teenagers in New York who are grappling with what aging out will mean for them and meets a woman who has parented eleven kids from the system, almost all over the age of eighteen, and all still in desperate need of a sense of home and belonging. This book focuses intensely on a few foster families who are deeply invested in the system's success, and attempts to humanize and challenge a broken system, while at the same time is a tribute to resiliency and offers hope for real change. -- Publisher's description.